PENGARUH LITERASI EKONOMI DAN TREN FEAR OF MISSING OUT (FoMO) TERHADAP PERILAKU KONSUMTIF MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS PALANGKA RAYA: The Influence of Economic Literacy and the Fear of Missing Out (FoMO) Trend on the Consumptive Behavior of Students in the Economic Education Study Program at the University of Palangka Raya - Tambunan, Herta; Uda, Tonich; Rakhmawati, Dewi; Eriawaty, Eriawaty (Ganec Swara, 2025)
The phenomenon of consumer beha.vior a.mong students is increa.sing, especia.lly due to low economic litera.cy a.nd high exposure to socia.l media. tha.t triggers a.nxiety a.bout being left behind by the socia.l trend of fea.r of missing out (FoMO). This study a.ims to a.na.lyze the influence of economic litera.cy a.nd the trend of fea.r of missing out (FoMO) on the consumer beha.vior of students in the Economics Educa.tion Study Progra.m, Fa.culty of Tea.cher Tra.ining a.nd Educa.tion, Pa.la.ngka. Ra.ya. University. This study uses a. qua.ntita.tive a.pproa.ch with a. survey method by distributing questionna.ires to 50 students a.s a. ra.ndomly selected sa.mple. The da.ta. were a.na.lyzed using multiple linea.r regression techniques to see the simulta.neous a.nd pa.rtia.l effects between economic litera.cy a.nd fea.r of missing out (FoMO) on consumer beha.vior. The results of the study indica.te tha.t there is no influence of economic litera.cy on consumer beha.vior of students of the Economics Educa.tion Study Progra.m, Pa.la.ngka. Ra.ya. University. While the fea.r of missing out (FoMO) trend ha.s a. significa.nt influence on consumer beha.vior of students of the Economics Educa.tion Study Progra.m, Pa.la.ngka. Ra.ya. University. The coefficient of determina.tion (R2 ) of economic litera.cy, a.nd fea.r of missing out on consumer beha.vior of students of the Economics Educa.tion Study Progra.m, Faculty of Teacher Training and Education, Palangka Raya University is 0.677 or 67.7%.